Dissemination of a IncHI2A plasmid co-harboring the mcr-9 and bla NDM-1 genes in Israeli hospitals - Amos Adler; Stefany Ayala-Montaño; Mark V. Assous; Yuval Geffen; Sandra Reuter (Annals of Clinical Microbiology and Antimicrobials)
Abstract The mcr-9 allele is typically located on IncHI2 type plasmids, but there are only few reports describing the co-occurrence of the bla NDM gene on the same plasmid. Our aims were to describe the spread of an IncHI2A plasmid harboring both the mcr-9 and the bla NDM-1 genes in a multicenter study in Israel. All New-Delhi Metallo-β-lactamase-producing Enterobacterales (NDME) isolated from three medical centres in Israel between January 2018 and July 2019 were included. The mcr-9.1 gene was identified in 37/212 (17.4%) of the isolates, mostly in Enterobacter cloacae (34/37, 92%). The mcr-9.1 gene was also identified in Klebsiella pneumoniae sequence types (ST)-76 (n = 2) and Escherichia coli ST-69 (n = 1). In one hospital, out of 32 E. cloacae isolates, 19 (51.35%) were clustered into five transmission clusters of the ST-511, ST-1261 and ST-1750. Four subtypes of a ~ 290 kb IncHI2A type plasmid were identified in all isolates that co-harbored the mcr-9.1 and the bla NDM-1 genes. This plasmid was identified in all isolates, with four sub-communities (sc), with sc-4 identified in all three species. The resistance genes were surrounded by the IS26 (mcr-9.1) or by the ISAba125 and the IS300 (bla NDM-1) mobile elements. The dissemination of the mcr-9.1 and the bla NDM-1 genes was accelerated via clonal spread and the dual carriage on a single plasmid.